Supply and Demand Study for a Textile Production and Sewing Association - Ludeña-Pérez, Angela Fernanda (2022)
In the present investigative work, a market study was carried out in the Association of textile production and sewing ‘Lew Asolew’, in the city of Machala, Province of El Oro, with the aim of analyzing supply and demand. The applied methodology was descriptive, under the qualitative and quantitative approach, which consisted of a scientific bibliographic investigation, analyzing the study variables such as consumer behavior, the textile sector and the application of surveys to obtain the necessary information by of the selected population. The results reflect that the behavior of the market that affects the operation of the association, the following prevailing: the price that is established for each garment is in accordance with the quality and design, generating an influence on the customer's purchase decision. As a conclusion, it was identified that there is excess demand, that is, it is estimated that future demand is greater than supply; in such a way it is determined that there will be an unsatisfied demand.